Pengaruh Suku Bunga, Harga Emas, dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan (IHSG) Dengan Profitabilitas Sebagai Variabel Moderating - Wini Oktaviani (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine the effect of Interest Rates, Gold Prices and World Oil Prices on the Jakarta Composite Index (JCI) with Profitability as a Moderating Variable in LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024 using the Purpose Sampling method. The analytical method in this study is panel data regression analysis. The results of this study determine that Interest rates have a positive and significant effect on the JCI. Gold prices have a positive and significant effect on the JCI. World oil prices have a positive and significant effect on the JCI. Interest rates are moderated by Profitability and have a positive but insignificant effect on the JCI. Gold prices are moderated by Profitability and have a positive but insignificant effect on the JCI. World oil prices are moderated by Profitability and have a positive but insignificant effect on the JCI.